The Effect of Teacher Motivation in Mediating Commitment and Professional Competence on Teacher’s Performance of Vocational School in Blora Regency - Aji, Arya Pradita; Martono, S.; Fakhruddin, Fakhruddin (Educational Management, 2019)
Teacher performance is influenced by several factors, including teacher commitment, teacher profesional competence and teacher motivation, the higher the commitment, profesional competence and motivation of a teacher, the better the performance. The purpose of this study is to obtain concrete evidence about teacher motivation in mediating the effect of teacher commitment and teacher professional competence on learning outcomes. This research used a quantitative approach with a hypothesis study research design. The population of this study was 297 Vocational High School teachers in Blora Regency. The sampling technique used purposive sampling. So that a final sample of 109 people was obtained. Data analysis techniques using descriptive and inferential statistical analysis techniques. The results showed that commitment had a direct influence of 34% on teacher performance. Professional competence has a direct influence of 26.1% on teacher performance and teacher motivation has a direct effect of 44.5% on teacher performance. Commitment has an indirect effect of 11.1% through motivation on teacher performance and professional competence has an indirect effect of 24.2% through teacher motivation on teacher performance.